Perovskite thin film, preparation method thereof and perovskite solar cell
By using amidinothiourea and glycine hydrochloride as additives in perovskite solar cells, the problems of Sn2+ oxidation and asynchronous crystallization were solved, and high-quality large-area perovskite films were prepared, which improved the stability and efficiency of solar cells.
Patent Information
- Application Number
- CN202510001666.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-11
AI Technical Summary
The power conversion efficiency of single-junction perovskite solar cells is limited by the oxidation and asynchronous crystallization of Sn2+, resulting in poor film quality and performance.
Amidinothiourea and glycine hydrochloride are used as perovskite precursor additives to prevent defects caused by Sn4+ by extending the volatilization process of Sn4+, and the synergistic effect of Lewis base and zwitterionic ions is used to promote grain growth and carrier recombination life.
The high-quality, large-area perovskite films were prepared, the stability and photoelectric conversion efficiency of solar cells were improved, and the power conversion efficiency of no less than 21.02%.
Smart Images

Figure CN119604175A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite film and a preparation method thereof, and a perovskite solar cell. Background Art
[0002] So far, the power conversion efficiency (PCE) of single-junction perovskite solar cells (PSCs) has reached 26.7%, which is comparable to the efficiency of crystalline silicon cells. In order to make the PCE of single-junction or tandem solar cells close to the Shockley-Queisser (SQ) limit, it is common to prepare perovskite films by partially replacing lead with tin. However, Sn 2+ Pb 2+ has stronger Lewis acidity, resulting in Sn 2+ The reaction rate with AX (A=FA / MA, X=I) is faster. In the initial stage of crystallization, more Sn 2+ Participate in the reaction to form a rough Sn-rich surface. The characteristics of the Sn-rich surface further make the Sn-Pb mixed film easy to oxidize, resulting in the formation of Sn vacancies and poor carriers. In order to fully realize the photovoltaic potential of Sn-Pb perovskite, it is crucial to solve this asynchronous crystallization phenomenon. Moreover, the rapid crystallization characteristics of Sn-based narrow-bandgap perovskites make it difficult to obtain dense and high-quality films on a larger scale. At the same time, Sn 2+ Easily oxidized to Sn 4+ . By spontaneous reaction Sn 4+ ⇋ Sn 2+ + 2h + When driven, it will cause a large amount of p-type doping, releasing two holes into the valence band and destroying the optimal energy level arrangement. In order to solve this problem, some researchers have tried to use antioxidant additives containing tin species to inhibit Sn 2+ However, excess Sn 2+ Additives may deteriorate the morphology of Sn-Pb perovskite films.
[0003] Therefore, it is urgent to develop a new perovskite precursor additive for the preparation of Sn-Pb large-area perovskite films and solar cells. Summary of the invention
[0004] Based on this, it is necessary to provide a perovskite film and a preparation method thereof, and a perovskite solar cell to address the problem that it is difficult to obtain dense and high-quality films of Sn narrow-bandgap perovskites on a larger scale.
[0005] A perovskite film contains perovskite and an additive; the additive contains a Lewis base and a zwitterion.
[0006] In one embodiment, the Lewis base comprises guanylthiourea, and the zwitterion comprises glycine hydrochloride.
[0007] In the above-mentioned perovskite film, guanylthiourea and glycine hydrochloride are used as perovskite precursor additives, so that the obtained perovskite film is uniform, has a smooth surface and strong crystallinity; the use of guanylthiourea and glycine hydrochloride allows the perovskite film to be prepared into a large-area perovskite film with high quality and good performance, and then be applied to large-area photovoltaic cells, so that the large-area photovoltaic cells have the advantages of good stability and high conversion efficiency.
[0008] In one embodiment, the additive contains the guanylthiourea and the glycine hydrochloride.
[0009] In one embodiment, in the perovskite film, the molar content of the guanylthiourea is ≤0.75%, and the molar content of the glycine hydrochloride is ≤10%.
[0010] In one embodiment, the perovskite is a narrow bandgap perovskite, and the bandgap of the perovskite is less than 1.3 eV.
[0011] In one embodiment, the band gap of the perovskite is 1.25~1.27eV.
[0012] In one embodiment, the structure of the perovskite is Cs 0.1 FA 0.5 MA 0.4 Sn 0.5 Pb 0.5 I 3 .
[0013] In one embodiment, the area of the perovskite film is ≥ 1 cm 2 .
[0014] The present invention also provides a method for preparing the perovskite film, comprising the following steps: dissolving the perovskite precursor material and the additive in a solvent so that the concentration of the Lewis base is ≤0.75 mol% and the concentration of the zwitterion is ≤10 mol%, to obtain a perovskite precursor solution; scraping the perovskite precursor solution into a wet film, quenching, and annealing to obtain the film.
[0015] In one embodiment, the perovskite precursor material includes SnI 2 、PbI 2 , FAI, MAI, CsI, Sn powder and SnF 2 At least one of .
[0016] Conventional perovskite precursor additives inhibit oxygen-induced Sn2+ To Sn 4+ to inhibit the transformation process of Sn 4+ The defects of perovskite films and perovskite solar cells caused by Sn 2+ To Sn 4+ The reaction equation for the conversion is as follows:
[0017] .
[0018] The method for preparing the perovskite film of the present invention uses guanylthiourea and glycine hydrochloride as perovskite precursor additives, which is to generate Sn 4+ Converted into chloride and volatilized (during the annealing process, chloride ions combine with protons and volatilize in the form of hydrogen chloride gas) to prevent Sn 4+ The defects of perovskite films and perovskite solar cells are caused by this. FATU and GlyHCl can undergo a solid-solid phase reaction, and this reaction can be used to extend the processing window of the scraped Sn-Pb perovskite film, providing sufficient time for the film-making process, and thus high-quality, large-area perovskite films can be prepared. The reaction principle is as follows:
[0019] .
[0020] The preparation method of the perovskite film of the present invention effectively reduces the Sn content in the process of preparing the perovskite precursor solution, depositing the perovskite film and storing the perovskite film. 4+ related defects and extend the shelf life of the device under ambient conditions.
[0021] The preparation method of the perovskite film of the present invention utilizes the synergistic effect of Lewis base and zwitterion double additives to obtain high-quality Cs 0.1 FA 0.5 MA 0.4 Sn 0.5 Pb 0.5 I 3 Mixed perovskite film. Adding dual additives at the same time can also solve the problem of asynchronous crystallization of Sn and Pb, and can promote grain growth, prolong the carrier recombination life, and thus increase the open circuit voltage ( V OC ), the photovoltaic device prepared by the method for preparing the perovskite film of the present invention can achieve a high power conversion efficiency of not less than 21.02%.
[0022] The present invention also provides a perovskite solar cell, comprising the perovskite film as described above.
[0023] In one embodiment, the perovskite solar cell includes a first electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer, and a second electrode layer stacked in sequence from bottom to top; the perovskite light absorption layer includes the perovskite film as described above.
[0024] In one embodiment, the first electrode layer is a transparent conductive layer, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer.
[0025] In one of the embodiments, the photoelectric conversion efficiency of the perovskite solar cell is ≥21.02%.
[0026] The present invention also provides a method for preparing the perovskite solar cell, comprising the following steps: Prepare a first electrode layer; prepare a hole transport layer; prepare a perovskite light absorbing layer: dissolve a perovskite precursor material and the additive in a solvent so that the concentration of the Lewis base is ≤0.75 mol%, and the concentration of the zwitterion is ≤10 mol%, to obtain a perovskite precursor solution; scrape the perovskite precursor solution into a wet film, extract, anneal, and obtain a perovskite light absorbing layer; prepare an electron transport layer; prepare a second electrode layer.
[0027] In one embodiment, the coating speed is 5-10 mm / s.
[0028] In one embodiment, the quenching method is nitrogen quenching.
[0029] In one embodiment, the annealing method is specifically: annealing at 50-60° C. for 2-5 min, and then annealing at 90-110° C. for 6-8 min.
[0030] In one embodiment, the solvent contains DMF and DMSO, and the volume ratio of DMF and DMSO is (1-7): 1. This is a volume ratio under normal temperature and pressure conditions.
[0031] The present invention also provides a photovoltaic module, comprising the perovskite solar cell as described above.
[0032] The present invention also provides an electrical device, comprising the perovskite solar cell as described above.
[0033] The present invention also provides a power generation device, comprising the perovskite solar cell as described above.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] A perovskite film and a preparation method thereof, and a perovskite solar cell of the present invention use guanylthiourea and glycine hydrochloride as perovskite precursor additives, so that the obtained perovskite film is uniform, has a smooth surface and strong crystallinity; the use of guanylthiourea and glycine hydrochloride allows the perovskite film to be prepared into a large-area perovskite film with high quality and good performance, and then be applied to large-area photovoltaic cells, so that the large-area photovoltaic cells have the advantages of good stability and high conversion efficiency. In the preparation method of the perovskite film of the present invention, guanylthiourea and glycine hydrochloride are used as perovskite precursor additives, and the generated Sn 4+ Converted into chloride and volatilized (during the annealing process, chloride ions combine with protons and volatilize in the form of hydrogen chloride gas) to prevent Sn 4+ The defects of the perovskite film and the perovskite solar cell caused by the above method are eliminated. Amidothiourea (FATU) and glycine hydrochloride (GlyHCl) can undergo a solid-solid phase reaction, and this reaction is used to extend the processing window of the scraped Sn-Pb perovskite film, providing sufficient time for the film-making process, thereby preparing a high-quality, large-area perovskite film. The preparation method of the perovskite film of the present invention effectively reduces the Sn content in the process of preparing the perovskite precursor solution, depositing the perovskite film and storing the perovskite film. 4+ The method for preparing the perovskite film of the present invention utilizes the synergistic effect of Lewis base and zwitterion double additives to obtain high-quality Cs 0.1 FA 0.5 MA 0.4 Sn 0.5 Pb 0.5 I 3 Mixed perovskite film. Adding dual additives at the same time can also solve the problem of asynchronous crystallization of Sn and Pb, and can promote grain growth, prolong the carrier recombination life, and thus increase the open circuit voltage ( V OC ), the photovoltaic device prepared by the preparation method of the perovskite film of the present invention can achieve a high power conversion efficiency of not less than 21.02%. The preparation method of the perovskite film of the present invention has the advantages of mild and controllable preparation conditions, simple preparation method, low cost, and applicability to the preparation of large-area perovskite solar cell modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell according to the present invention;
[0037] Figure 2 Schematic diagram of the process flow for preparing perovskite film and perovskite light absorbing layer;
[0038] Figure 3Comparison diagram of the perovskite wet film and the mesophase film of Comparative Example 1 and Example 2 in Experimental Example 1. (a) and (b) are the perovskite wet film and the mesophase film of Comparative Example 1, respectively. (c) and (d) are the perovskite wet film and the mesophase film of Example 2, respectively. ;
[0039] Figure 4 The figures are comparison diagrams of the perovskite films of Comparative Example 1 and Example 2 in Experimental Example 2, wherein (a) is the front side of the perovskite film of Comparative Example 1, (b) is the perovskite film of Comparative Example 1 observed through the glass substrate side, (c) is the front side of the perovskite film of Example 2, and (d) is the perovskite film of Example 2 observed through the glass substrate side;
[0040] Figure 5 The optical microscope observation comparison diagrams of the perovskite films of Comparative Examples 1 to 3 and Example 2 in Experimental Example 3, the observation object in (a) is the perovskite film prepared in Comparative Example 1, the observation object in (b) is the perovskite film prepared in Comparative Example 2, the observation object in (c) is the perovskite film prepared in Comparative Example 3, and the observation object in (d) is the perovskite film prepared in Example 2;
[0041] Figure 6 The scanning electron microscope comparison diagrams of the perovskite films of Comparative Examples 1 to 3 and Example 2 in Experimental Example 4, wherein the observation object in (a) is the perovskite film prepared in Comparative Example 1, the observation object in (b) is the perovskite film prepared in Comparative Example 2, the observation object in (c) is the perovskite film prepared in Comparative Example 3, and the observation object in (d) is the perovskite film prepared in Example 2;
[0042] Figure 7 The photoluminescence (PL) spectra and time-resolved photoluminescence (TRPL) spectra of the perovskite films of Example 2 and Comparative Examples 1 to 3 in Experimental Example 5, (a) is the photoluminescence spectrum, (b) is the time-resolved photoluminescence spectrum, wherein Pristine represents that the detection object is the perovskite film prepared in Comparative Example 1, FATU represents that the detection object is the perovskite film prepared in Comparative Example 2, GlyHCl represents that the detection object is the perovskite film prepared in Comparative Example 3, and FATU+GlyHCl represents that the detection object is the perovskite film prepared in Example 2;
[0043] Figure 8 is the XRD curve diagram of the perovskite film of Example 2 and Comparative Examples 1 to 3 in Experimental Example 6, wherein Pristine represents that the detection object is the perovskite film prepared in Comparative Example 1, FATU represents that the detection object is the perovskite film prepared in Comparative Example 2, GlyHCl represents that the detection object is the perovskite film prepared in Comparative Example 3, and FATU+GlyHCl represents that the detection object is the perovskite film prepared in Example 2;
[0044] Fig. 9 It is a comparison chart of the stability test results of the perovskite solar cells in Example 4 and Comparative Examples 4 to 6 in Experimental Example 7, wherein Pristine represents that the test object is the perovskite solar cell prepared in Comparative Example 4, FATU represents that the test object is the perovskite solar cell prepared in Comparative Example 5, GlyHCl represents that the test object is the perovskite solar cell prepared in Comparative Example 6, and FATU+GlyHCl represents that the test object is the perovskite solar cell prepared in Example 4;
[0045] Fig.10 The perovskite solar cells in Example 4 and Comparative Examples 4 to 6 in Experimental Example 8 JV Curve comparison diagram, wherein Pristine represents that the detection object is the perovskite solar cell prepared in Comparative Example 4, FATU represents that the detection object is the perovskite solar cell prepared in Comparative Example 5, GlyHCl represents that the detection object is the perovskite solar cell prepared in Comparative Example 6, and FATU+GlyHCl represents that the detection object is the perovskite solar cell prepared in Example 4;
[0046] Fig.11 The perovskite solar cells in Example 4 and Comparative Examples 4 to 6 in Experimental Example 8 JV Comparison chart of test data, wherein Pristine represents the perovskite solar cell prepared in Comparative Example 4, FATU represents the perovskite solar cell prepared in Comparative Example 5, GlyHCl represents the perovskite solar cell prepared in Comparative Example 6, and FATU+GlyHCl represents the perovskite solar cell prepared in Example 4;
[0047] Fig.12 Schematic diagram of laser scribing of perovskite solar cells (a), actual image of perovskite solar cells (b), and optical microscope image of laser scribing (c);
[0048] Fig.13 The Mott-Schottky curve diagram (a), the open circuit voltage versus light intensity curve diagram (b) and the Nyquist curve diagram (c) of the components of the perovskite solar cells of Example 4 and Comparative Examples 4 to 6 in Experimental Example 9 after scribing and encapsulation, and the illustration in (c) is an equivalent circuit diagram, wherein Pristine represents that the detection object is the component corresponding to Comparative Example 4, FATU represents that the detection object is the component corresponding to Comparative Example 5, GlyHCl represents that the detection object is the component corresponding to Comparative Example 6, and FATU+GlyHCl represents that the detection object is the component corresponding to Example 4;
[0049] Fig.14The stability test diagram of the perovskite solar cell components after scribing of Example 4 (Target) and Comparative Example 4 (Pristine) in Experimental Example 10 and JV In the curve graph, the detection object in (a) is an unpackaged component, the detection object in (b) is an unpackaged component, and the detection object in (c) is a packaged component;
[0050] Fig.15 The components of the perovskite solar cells after scribing and packaging in Example 4 (Pristine) and Comparative Example 4 (Target) in Experimental Example 10 are JV Graphs;
[0051] Fig.16 This is a comparison chart of photovoltaic parameters of the components of the perovskite solar cells after scribing and packaging in Example 4, Comparative Examples 7 and 8 in Experimental Example 11;
[0052] Fig.17 This is a comparison chart of photovoltaic parameters of the components of the perovskite solar cells after scribing and packaging in Example 4 and Comparative Examples 9 to 13 in Experimental Example 11. DETAILED DESCRIPTION
[0053] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0055] The reagents used in the following examples, unless otherwise specified, are all commercially available; the methods used in the following examples, unless otherwise specified, are all achievable by conventional methods.
[0056] Example 1
[0057] A perovskite film, comprising perovskite and an additive; the additive comprises guanylthiourea and glycine hydrochloride; the molar content of guanylthiourea in the perovskite film is ≤0.75%, and the molar content of glycine hydrochloride is ≤10%; the band gap of the perovskite is <1.3 eV, and the area of the perovskite film is ≥1 cm 2 .
[0058] Example 2
[0059] A method for preparing a perovskite film, such as Figure 2 As shown, the following steps are included:
[0060] 1. Pretreatment of the substrate: Use a laser etcher to etch the edge of the ITO (indium tin oxide) conductive glass, leaving the cathode position, and then use detergent, deionized water and ethanol to clean it in turn (the area of ITO is 0.25*0.25 cm 2 , thickness is 0.11 mm, sheet resistance is 15 Ω / sq), each cleaning takes 15 minutes to obtain a substrate / transparent conductive layer (ie, base).
[0061] 2. Prepare perovskite precursor solution: Weigh the perovskite precursor materials: SnI 2 、PbI 2 , FAI, MAI, CsI, Sn powder, SnF 2 The additives FATU (guanylthiourea, CAS No.: 2114-02-5, purchased from McLean) and GlyHCl (glycine hydrochloride, CAS No.: 6000-43-7, purchased from Aladdin) were dissolved in 0.6 mL of a DMF / DMSO mixed solvent (the volume ratio of DMF to DMSO was 4:1), and stirred evenly to obtain a narrow bandgap perovskite precursor solution with a concentration of 1.2 M.
[0062] 3. Preparation of perovskite light-absorbing layer: Take the above narrow bandgap perovskite precursor solution, stir it for more than 5 hours, and then evenly scrape it on the above transparent conductive layer at a scraper speed of 7 mm / s to obtain a perovskite wet film (fresh perovskite film); use high-purity nitrogen (purity: 99.999%) to assist a high-pressure air gun to quench the perovskite wet film to obtain a brown intermediate phase film; anneal at 50°C for 3 minutes, and then anneal at 100°C for 7 minutes to obtain a perovskite film.
[0063] Example 3
[0064] A perovskite solar cell comprises a first electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer, and a second electrode layer stacked in sequence from bottom to top; the perovskite light absorption layer comprises the perovskite film shown in Example 1, the first electrode layer is a transparent conductive layer, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer; a passivation layer is further provided between the perovskite light absorption layer and the second charge transport layer. The photoelectric conversion efficiency of the perovskite solar cell is ≥21.02%.
[0065] Example 4
[0066] A method for preparing a perovskite solar cell comprises the following steps:
[0067] 1. Pretreatment of the substrate (preparation of the first electrode layer): Use a laser etcher to etch the edge of the ITO (indium tin oxide) conductive glass, leaving the cathode position, and then use detergent, deionized water and ethanol to clean it in turn (the area of ITO is 0.25*0.25 cm 2 , thickness is 0.11 mm, sheet resistance is 15 Ω / sq), each cleaning takes 15 minutes to obtain a substrate / transparent conductive layer (ie, base).
[0068] 2. Preparation of a hole transport layer: dissolving PEDOT:PSS in deionized water (the volume ratio of PEDOT:PSS to deionized water is 1:5) to obtain an aqueous solution of PEDOT:PSS; spin coating the aqueous solution of PEDOT:PSS on the transparent conductive layer at a rotation speed of 4000 rpm, and annealing at 150°C for 15 min in ambient air to obtain a substrate / transparent conductive layer / hole transport layer.
[0069] After annealing, the substrate / transparent conductive layer / hole transport layer were immediately transferred to a glove box filled with nitrogen. 2 O and O 2 The content is < 0.01ppm.
[0070] 3. Prepare perovskite precursor solution: Weigh the perovskite precursor materials: SnI 2 , PbI 2 , FAI, MAI, CsI, Sn powder, SnF 2 The additives FATU (guanylthiourea, CAS No.: 2114-02-5, purchased from McLean) and GlyHCl (glycine hydrochloride, CAS No.: 6000-43-7, purchased from Aladdin) were dissolved in 0.6 mL of a DMF / DMSO mixed solvent (the volume ratio of DMF to DMSO was 4:1), and stirred evenly to obtain a narrow bandgap perovskite precursor solution with a concentration of 1.2 M.
[0071] The structural formula of the perovskite in the narrow bandgap perovskite precursor solution is Cs 0.1 FA 0.5 MA 0.4 Pb 0.5 Sn 0.5 I 3 , the concentrations of additives FATU and GlyHCl were 0.75 mol % and 10 mol %, respectively.
[0072] 4. Preparation of perovskite light absorbing layer (such as Figure 2As shown): Take the above narrow bandgap perovskite precursor solution, stir it for more than 5 hours, and then evenly scrape it on the above hole transport layer at a scraper speed of 7 mm / s to obtain a perovskite wet film (fresh perovskite film); use high-purity nitrogen (purity: 99.999%) to assist a high-pressure air gun to quench the perovskite wet film to obtain a brown intermediate phase film; anneal at 50°C for 3 minutes, and then anneal at 100°C for 7 minutes to obtain a substrate / transparent conductive layer / hole transport layer / perovskite light absorbing layer.
[0073] 5. Passivate the perovskite light-absorbing layer: dissolve PEACl in isopropanol to obtain a 1 mg / mL PEACl solution; 2 Dissolved in a mixture of isopropanol and toluene (volume ratio of isopropanol to toluene is 1:1) to obtain 0.5 mg / mL EDAI 2 The PEACl solution was spin-coated onto the perovskite light-absorbing layer at a speed of 5000 rpm for 20 seconds, and then annealed at 100°C for 5 minutes. 2 The solution was prepared at a rotation speed of 5000 rpm and a spin coating time of 20 s, followed by annealing at 100°C for 5 min to obtain a substrate / transparent conductive layer / hole transport layer / perovskite light absorbing layer / 2D passivation layer.
[0074] 6. Preparation of electron transport layer: Dissolve PCBM powder in chlorobenzene to obtain a PCBM solution with a concentration of 10 mg / mL; Spin-coat the PCBM solution on the 2D passivation layer at a speed of 5000 rpm and cool to room temperature; In a vacuum system (< 5 × 10 -4 Pa), a 20 nm thick C 60 (Evaporation rate: 0.05-0.1 Å / s). Continue to deposit SnO using atomic layer deposition 2 The film was prepared under the following conditions: using tin (IV) dimethylamide as the tin source and water as the O source at 85 °C for 160 cycles to obtain a substrate / transparent conductive layer / hole transport layer / perovskite light absorbing layer / 2D passivation layer / electron transport layer.
[0075] 7. Prepare the second electrode layer: Use thermal evaporation to deposit a 150 nm thick metal Ag layer on the surface of the electron transport layer as the second electrode layer to obtain substrate / transparent conductive layer / hole transport layer / perovskite light absorbing layer / 2D passivation layer / electron transport layer / second electrode layer, that is, a perovskite solar cell.
[0076] Comparative Example 1
[0077] A method for preparing a perovskite film is substantially the same as that of Example 2, except that FATU and GlyHCl are not added to the perovskite precursor solution prepared in step 2.
[0078] Comparative Example 2
[0079] A method for preparing a perovskite film is basically the same as that of Example 2, except that only FATU is added to the perovskite precursor solution prepared in step 2.
[0080] Comparative Example 3
[0081] A method for preparing a perovskite film is basically the same as that of Example 2, except that only GlyHCl is added to the perovskite precursor solution prepared in step 2.
[0082] Comparative Example 4
[0083] A method for preparing a perovskite solar cell is basically the same as Example 4, except that FATU and GlyHCl are not added in the preparation of the perovskite precursor solution in step 3.
[0084] Comparative Example 5
[0085] A method for preparing a perovskite solar cell is basically the same as Example 4, except that only FATU is added to the perovskite precursor solution prepared in step 3.
[0086] Comparative Example 6
[0087] A method for preparing a perovskite solar cell is basically the same as Example 4, except that only GlyHCl is added to the perovskite precursor solution prepared in step 3.
[0088] Comparative Example 7
[0089] A method for preparing a perovskite solar cell is basically the same as Example 4, except that in step 3, the volume ratio of DMF to DMSO in preparing the perovskite precursor solution is 1:1.
[0090] Comparative Example 8
[0091] A method for preparing a perovskite solar cell, the preparation method is basically the same as that of Example 4, except that: in step 3, the volume ratio of DMF to DMSO in preparing the perovskite precursor solution is 7:1.
[0092] Comparative Examples 9-13
[0093] A method for preparing a perovskite solar cell, the preparation method is basically the same as Example 4, except that: in step 4 of preparing the perovskite light-absorbing layer, the scraper speeds for preparing the perovskite wet film are 5 mm / s, 6 mm / s, 8 mm / s, 9 mm / s, and 10 mm / s, respectively.
[0094] Experimental Example 1
[0095] Comparison of perovskite wet film and mesophase film without and with FATU and GlyHCl added to the perovskite precursor solution.
[0096] like Figure 3 As shown, Figure 3 (a) and Figure 3 (b) is the perovskite wet film and the mesophase film in Comparative Example 1, Figure 3 (c) and Figure 3 (d) is the perovskite wet film and the mesophase film in Example 2. Wherein, Figure 3 (a) is the perovskite wet film formed without adding FATU and GlyHCl to the perovskite precursor solution. Figure 3 (c) The perovskite wet film formed after adding FATU and GlyHCl to the perovskite precursor solution, both of which are transparent and light yellow; Figure 3 (b) is the intermediate phase film formed without adding FATU and GlyHCl to the perovskite precursor solution. Figure 3 (d) is the intermediate phase film formed after adding FATU and GlyHCl to the perovskite precursor solution, both of which are brown. Figure 3 The state of (a) changes to Figure 3 (b) state, the time required is 84 seconds; Figure 3 (c) The state changes to Figure 3 (d) The time required is 114 seconds. From the above comparison, it can be seen that without adding FATU and GlyHCl to the perovskite precursor solution, the time from the perovskite wet film to the intermediate phase film is shorter, and Figure 3 (b) It can be seen that pinholes appear on the intermediate phase film, indicating that the film formation effect is not good; in contrast, after adding FATU and GlyHCl to the perovskite precursor solution, the time from the perovskite wet film to the intermediate phase film is extended to 114 seconds, and from Figure 3 It can be seen in (d) that the intermediate phase film is a pinhole-free Sn-Pb perovskite film with larger grains.
[0097] The above comparison proves that the perovskite precursor solution with the additive of the present invention can not only prepare a perovskite film with better effect, but also extend the window period for preparing the perovskite film, providing more sufficient preparation time for the process of preparing large-area perovskite film.
[0098] Experimental Example 2
[0099] Comparison of the appearance of the perovskite films prepared in Example 2 and Comparative Example 1.
[0100] like Figure 4 As shown, the glass surface of the perovskite film prepared without adding FATU and GlyHCl to the titanium ore precursor solution ( Figure 4 (b) Green, the perovskite film glass surface prepared by adding FATU and GlyHCl ( Figure 4 (d) is grayish black, which is more likely to absorb light, thereby increasing the device current. This proves that the perovskite precursor solution with the additive of the present invention can slow down the crystallization of perovskite and is suitable for preparing large-area perovskite films.
[0101] Experimental Example 3
[0102] An optical microscope was used to observe the perovskite films without adding FATU and GlyHCl, with only FATU added, with only GlyHCl added, and with both FATU and GlyHCl added to the perovskite precursor solution.
[0103] like Figure 5 As shown in (a), the perovskite film prepared without adding FATU and GlyHCl to the perovskite precursor solution is relatively rough, contains small particles, and the film is uneven and has many micron-scale wrinkles. Figure 5 As shown in (d), the perovskite film prepared by adding FATU and GlyHCl to the perovskite precursor solution is the smoothest and has no wrinkles. The film-forming effect is better than that of the perovskite films in Comparative Examples 1 to 3.
[0104] Experimental Example 4
[0105] A scanning electron microscope (SEM, Thermo Scientific FEI) was used to observe the perovskite films without adding FATU and GlyHCl, with only FATU added, with only GlyHCl added, and with both FATU and GlyHCl added to the perovskite precursor solution.
[0106] like Figure 6 As shown, it can be seen that the perovskite film prepared without adding FATU and GlyHCl to the titanium ore precursor solution exhibits a larger pore morphology, significant surface roughness and smaller grains (about 200 nanometers on average); the grain size of the perovskite film prepared after adding FATU and GlyHCl increases from 200 nanometers to 800 nanometers.
[0107] Experimental Example 5
[0108] The steady-state photoluminescence (PL) and time-resolved photoluminescence (TRPL) spectra of the perovskite films were measured using an Edinburgh FLS1000 fluorescence spectrometer equipped with a PMT980 detector and a VPL450 laser.
[0109] like Figure 7 (a) shows the incident excitation light. The PL emission intensity of the FATU+GlyHCl film is about three times that of the original sample, which indicates that FATU+GlyHCl reduces the non-radiative recombination in the Sn-Pb mixed perovskite film. Figure 7 As shown in (b), the average decay lifetime of TRPL is τ ave (FATU+GlyHCl) = 215.0 ns > τ ave (FATU) = 153.4ns > τ ave (original) = 64.8 ns. This indicates that the introduction of the dual additives FATU+GlyHCl greatly suppressed carrier trapping.
[0110] Experimental Example 6
[0111] X-ray diffractometer (XRD, Bruker D8 Advance) was used to detect the XRD curves of the perovskite films prepared after no FATU and GlyHCl were added to the perovskite precursor solution (Comparative Example 1), only FATU was added (Comparative Example 2), only GlyHCl was added (Comparative Example 3), and FATU and GlyHCl were added (Example 2).
[0112] like Figure 8 As shown, the perovskite film prepared after adding FATU and GlyHCl has the strongest crystallinity.
[0113] Experimental Example 7
[0114] Testing the stability of perovskite solar cells.
[0115] The perovskite solar cells prepared in Example 4 and Comparative Examples 4 to 6 were placed in a nitrogen environment and stored for 1200 hours. The results are as follows: Fig. 9 As shown, the perovskite solar cell module prepared after adding FATU and GlyHCl still maintains more than 98% of the initial PCE.
[0116] Experimental Example 8
[0117] The perovskite solar cells prepared in Example 4 and Comparative Examples 4 to 6 were tested using a solar simulator. JV curve.
[0118] like Fig.10 and Fig.11As shown in the figure, the photoelectric conversion efficiency (PCE) of the perovskite solar cell (Pristine) prepared without adding FATU and GlyHCl to the perovskite precursor solution is 15.37% (forward scan, V OC = 0.797 V, J SC = 27.45mA / cm 2 , FF = 0.70). The photoelectric conversion efficiency of the perovskite solar cell (FATU+GlyHCl) prepared by adding FATU and GlyHCl to the perovskite precursor solution reached 21.02% (forward scan, V OC = 0.850 V, J SC = 32.70 mA / cm 2 , FF = 0.76), with almost no hysteresis effect.
[0119] Experimental Example 9
[0120] The Mott-Schottky curves, open circuit voltage (V) and the like of the components of the perovskite solar cells prepared in Example 4 and Comparative Examples 4 to 6 were measured using an electrochemical workstation under atmospheric room temperature. V OC ) Curve that changes with light intensity, Nyquist curve.
[0121] According to conventional processes, the perovskite solar cells of Example 4 and Comparative Examples 4 to 6 were laser etched to prepare perovskite solar cell modules (with an effective working area of 0.113 cm 2 , Fig.12 (a) is a schematic diagram of laser scribing. Fig.12 (c) is an optical microscope image of the laser scribed lines P1, P2, and P3. The dead zone width is 175.5 μm and the sub-cell width is 6 mm. From this, it can be calculated that the high geometric fill factor (GFF) is 97.1%. The following tests are performed on the component.
[0122] like Fig.13 As shown in (a), it can be seen that the addition of FATU increases the built-in potential of the original PSCs ( V bi ) increased from 0.458 V to 0.544 V. By adding FATU+GlyHCl, due to the reduction of trap-assisted recombination losses, V bi increases to 0.665 V, which is consistent with the higher V OC Corresponding. Fig.13As shown in (b), the ideal factors (n) of the original (pristine), FATU-added, GlyHCl-added, and FATU+GlyHCl-modified PSCs are calculated to be 1.57, 1.45, 1.44, and 1.40, respectively. The low n value of FATU+GlyHCl-modified PSCs indicates that trap-assisted recombination is effectively suppressed. It is confirmed that the oriented growth of FATU+GlyHCl-modified perovskite films reduces Sn vacancy defects, improves crystallinity and shows significantly enhanced stability. In order to deeply study the charge recombination dynamics at the device level, the electrochemical impedance spectroscopy (EIS) of PSCs at an applied voltage of 0-0.9V was recorded, and the complex impedance data provided an accurate and detailed image of the equivalent circuit resistance. Fig.13 (c) shows representative complex impedance scans of solar cell devices made with pristine, FATU-added, and FATU+GlyHCl-treated perovskite films at 0.5 V bias. S ) is very small, and the parallel resistance represented by the diameter of the main semicircular feature is reduced from 3000Ω·cm of the original film. 2 Increased to 3650Ω·cm for FATU treatment 2 and 8.3×10 treated with FATU+GlyHCl 4 Ω·cm². Under the measurement conditions, the shunt resistance (R rec ) can be interpreted as the shunt resistance of the perovskite layer, and the higher values for the FATU and FATU+GlyHCl treated layers reflect the observed improved crystallinity and suppressed charge recombination losses.
[0123] Experimental Example 10
[0124] The stability and JV Characteristics. Current density-voltage ( JV ) characteristics were obtained under a solar simulator (Newport, Class AAA) using a Keithley 2400 source meter at 100mWcm -2 The measurements were carried out under a light intensity of 1000 V and the light intensity was calibrated by a standard silicon battery (91150 V).
[0125] According to conventional processes, the perovskite solar cells of Example 4 and Comparative Examples 4 to 6 were laser etched to prepare perovskite solar cell modules (with an effective working area of 0.113 cm 2 , Fig.12 (a) is a schematic diagram of laser scribing. Fig.12(c) is an optical microscope image of the laser-scribed lines P1, P2, and P3. The dead zone width is 175.5 μm and the sub-cell width is 6 mm. From this, it can be calculated that the high geometric fill factor (GFF) is 97.1%. The following tests are performed on the component.
[0126] Fig.14 (a) Unencapsulated PSMs at ~85℃, N 2 Thermal stability test results under the conditions of Fig.14 (b) is the unencapsulated PSMs at RT and N 2 Storage stability under conditions Fig.14 (c) shows the storage stability of encapsulated PSMs exposed to RT, ~45% RH and air. It can be seen that FATU+GlyHCl modified perovskite solar modules (PSMs) exhibit better thermal stability (at 85 °C N 2 atmosphere, unencapsulated), still maintained 68% of its initial PCE after 400 h, while the PSMs without FATU+GlyHCl modification stopped functioning properly after about 160 h ( Fig.14 (a)). After 20 days of observation, the degradation area of the Ag electrode at the P1, P2 and P3 lines of the PSMs (Target) modified with FATU+GlyHCl in Example 4 was significantly smaller than that of the PSMs (Pristine) in Comparative Example 4. This indicates that the chemical reaction between Ag and the volatile decomposition products or halide anions (such as halides or halogen species) in the perovskite layer is reduced. 2 The 650-hour storage stability test in the glove box showed that the PSMs (Target) of Example 4 modified with FATU+GlyHCl maintained 94% of its initial PCE, while the PSMs (Pristine) of Comparative Example 4 only maintained 68% ( Fig.14 The optimized package assembly also exhibited excellent air storage stability, maintaining more than 81% of its initial efficiency after 430 hours, while the PSMs (Pristine) of Comparative Example 4 only maintained 64% ( Fig.14 (c)).
[0127] like Fig.15 As shown, compared with the perovskite solar cell module prepared without adding FATU and GlyHCl to the perovskite precursor solution (Comparative Example 4), the perovskite solar cell module prepared after adding FATU and GlyHCl to the perovskite precursor solution (Example 4) has a photoelectric conversion efficiency (PCE) of 16.83%, almost no loss in open circuit voltage, and an aperture area of 21.02 cm 2 , the steady-state output (SPO) efficiency at the maximum power point is 90% of the initial efficiency.
[0128] Experimental Example 11
[0129] The components prepared from the perovskite solar cells of Example 4 and Comparative Examples 7 to 13 were tested under AM1.5 G illumination using a solar simulator. JV ) characteristics were obtained under a solar simulator (Newport, Class AAA) using a Keithley 2400 source meter at 100mWcm -2 The measurements were carried out under a light intensity of 1000 V and the light intensity was calibrated by a standard silicon battery (91150 V).
[0130] According to conventional processes, the perovskite solar cells of Example 4 and Comparative Examples 4 to 13 were laser etched and packaged to prepare perovskite solar cell modules (with an effective working area of 0.113 cm 2 , Fig.12 (a) is a schematic diagram of laser scribing. Fig.12 (c) is an optical microscope image of the laser scribed lines P1, P2, and P3. The dead zone width is 175.5 μm and the sub-cell width is 6 mm. From this, it can be calculated that the high geometric fill factor (GFF) is 97.1%. The following tests are performed on the package components.
[0131] like Fig.16 As shown, compared with Comparative Examples 7 and 8, when the volume ratio of DMF to DMSO is 4:1, the performance of the prepared component in Example 4 is the best.
[0132] like Fig.17 As shown, compared with Comparative Examples 9 to 13, when the scraper speed for preparing the perovskite wet film in Example 4 is 7 mm / s, the performance of the component is the best.
[0133] In summary, the present invention proposes an effective method for preparing a perovskite film and a method for preparing a perovskite solar cell, uses a doctor blade coating method to prepare a narrow bandgap Sn-Pb mixed perovskite film and a solar cell, and utilizes the synergistic effect of Lewis base and zwitterion double additives to obtain high-quality Cs 0.1 FA 0.5 MA 0.4 Sn 0.5 Pb 0.5 I 3 Mixed perovskite film. Adding dual additives simultaneously not only solves the problem of asynchronous crystallization of Sn and Pb, but also reduces the Sn generated by oxidation. 4+ , can also promote grain growth, prolong carrier recombination lifetime, and thus increase the open circuit voltage of the device ( V OC). FATU and GlyHCl can undergo a solid-solid phase reaction, and this reaction is used to extend the processing window of blade-coated Sn-Pb perovskite films. Based on the effect of FATU+GlyHCl dual additives in slowing down the crystallization rate, it is beneficial to prepare large-area perovskite films and components, and there is almost no loss in open-circuit voltage, and the hysteresis is relatively small. Both encapsulated and unencapsulated components show excellent stability.
[0134] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0135] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite film, characterized in that: Contains perovskite and an additive; the additive contains a Lewis base and a zwitterion.
2. The perovskite film according to claim 1, characterized in that The Lewis base includes guanylthiourea, and the zwitterion includes glycine hydrochloride.
3. The perovskite film according to claim 2, characterized in that: In the perovskite film, the molar content of the guanylthiourea is ≤0.75%, and the molar content of the glycine hydrochloride is ≤10%.
4. The method for preparing a perovskite thin film according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: dissolving a perovskite precursor material and the additive in a solvent so that the concentration of the Lewis base is less than or equal to 0.75 mol% and the concentration of the zwitterion is less than or equal to 10 mol% to obtain a perovskite precursor solution; scraping the perovskite precursor solution into a wet film, quenching, and annealing to obtain the product.
5. A perovskite solar cell, characterized in that: Comprising the perovskite film as described in any one of claims 1 to 3.
6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The steps include: preparing a first electrode layer; preparing a hole transport layer; Preparing a perovskite light-absorbing layer: dissolving a perovskite precursor material and the additive in a solvent so that the concentration of the Lewis base is ≤0.75 mol% and the concentration of the zwitterion is ≤10 mol%, to obtain a perovskite precursor solution; scraping the perovskite precursor solution into a wet film, quenching, and annealing to obtain a perovskite light-absorbing layer; preparing an electron transport layer; The second electrode layer is prepared.
7. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The speed of the scraping is 5-10 mm / s.
8. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The annealing method is specifically: annealing at 50-60° C. for 2-5 min, and then annealing at 90-110° C. for 6-8 min.
9. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The solvent contains DMF and DMSO, and the volume ratio of DMF to DMSO is (1-7):
1.
10. A photovoltaic module, characterized in that: Comprising the perovskite solar cell as claimed in claim 5.